“Propuesta de acompañamiento en la fe desde la espiritualidad salesiana para los estudiantes del tercer ciclo de la carrera de sistemas de la Universidad Politécnica Salesiana sede Cuenca” - Leguízamo Bohórquez, María Anaís (2014)
This project is aimed at a group of students from the Systems Engineering at the UPS- Cuenca to show their experiences of Christian Spirituality and Salesian spirituality in their lives. The research involved 70 second cycle students from the School of Systems Engineering who were administered a questionnaire via Internet on various youth issues they are facing. Support was given through the teachings of the Church and Salesian charisma strategies through in person and online group support. For personnel working in the Listening Center they will be reenergized through social networks such as mobile chat applications and chat groups created on Facebook.